Understanding the AIDA Model in Marketing Small Business in the Digital Age: Opportunities and Challenges - Yuli Purbaningsih; Seprianti Eka Putri; B.M.A.S. Anaconda Bangkara; Agus Nurofik; M. Zahari MS (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Understanding small business marketing strategies in the technology era is very helpful for large and small business drivers. So, through this study, we have understood the AIDA marketing model among MSME drivers, primarily through document and literature searches in various publications, including books, scientific journals, and other publications related to the issues of the AIDA model and marketing of small business products. We cannot do that much data, up to 100 books, without going through a data analysis process that involves coding the data, evaluating interpretations, and drawing valid conclusions to answer the current question. Based on the results of the study and discussion, it can be concluded that the understanding and application of the AIDA marketing model for marketing MSME products and services in the digital era is very profitable; This model approach also has advantages and also drawnbacks.